The political economy of environmental policy reform in Latin America - Kaimowitz, D. (1996)
This article analyzes why it has been easier to promote some types of environmental policy reform in Latin America than others. It first looks at the main groups that might promote such reforms - developed country organizations, the urban middle class, groups that have direct material interests in reform, and movements for social justice. Then in looks at how the existing patterns of development in Latin America condition the prospects for reform, particular the region's great dependence on the exploitation of natural resources and the overall context of economic liberalization and structural adjustment. Finally, it examines how political factors, such as the degree of democratization favor or hinder environmental policy reform.